Geodesic acoustic mode (GAM) like oscillations and RMP effect in the STOR-M tokamak. (21st December 2017) - Basu, Debjyoti; Nakajima, Masaru; Melnikov, A.V.; McColl, David; Rohollahi, Akbar; Elgriw, Sayf; Xiao, Chijin; Hirose, Akira
Abstract: A new kind of quasi-coherent mode was observed in ohmic plasma in the STOR-M tokamak. It is featured with a clear solitary peak around 30–35 kHz in the power spectra of the ion saturation current ( I s a t ) of Langmuir probe as well as poloidal and toroidal mode numbers ( m = 1, n = 0) as per the prediction of conventional geodesic acoustic mode (GAM) theory. The dispersion relation of the mode is also similar to GAM and it also shows collisional damping. In contrast to conventional GAM, the floating potential ϕ of the observed GAM-like mode does not show similar symmetric poloidal and toroidal mode numbers ( m = 0, n = 0), but has ( m = 1, n = 1). The GAM-like mode has also a pronounced magnetic component with mixed poloidal modes ( m = 3 a n d m = 5 ; n = 1 ), as observed by Mirnov coils. This mode is suppressed by the application of resonance magnetic perturbations.